Demographic partitioning of dynamic energy subsidies revealed with an Ornstein–Uhlenbeck space use model. Issue 4 (29th March 2022) - Eisaguirre, Joseph M.; Booms, Travis L.; Barger, Christopher P.; Lewis, Stephen B.; Breed, Greg A.
Abstract: In populations across many taxa, a large fraction of sexually mature individuals do not breed but are attempting to enter the breeding population. Such individuals, often referred to as "floaters, " can play critical roles in the dynamics and stability of these populations and buffer them through periods of high adult mortality. Floaters are difficult to study, however, so we lack data needed to understand their roles in the population ecology and conservation status of many species. Here, we analyzed satellite telemetry data with a newly developed mechanistic space use model based on an Ornstein–Uhlenbeck process to help overcome the paucity of data in studying the differential habitat selection and space use of floater and territorial golden eagles Aquila chrysaetos . Our sample consisted of 49 individuals tracked over complete breeding seasons across 4 years, totaling 104 eagle breeding seasons. Modeling these data mechanistically was required to disentangle key differences in movement and particularly to separate aspects of movement driven by resource selection from those driven by use of a central place. We found that floaters generally had more expansive space use patterns and larger home ranges, as well as evidence that they partition space with territorial individuals seemingly on fine scales through differential habitat and resource selection. Floater and territorial eagle home ranges overlapped markedly, suggesting that floaters use the interstices between territories. Furthermore, floater and territorial eagles differed in how they selected for uplift variables, key components of soaring birds' energy landscape, with territorial eagles apparently better able to find and use thermal uplift. We also found relatively low individual heterogeneity in resource selection, especially among territorial individuals, suggesting a narrow realized niche for breeding individuals, which varied from the level of among‐individual variation present during migration. This work furthers our understanding of floaters' potential roles in the population ecology of territorial species and suggests that conserving landscapes occupied by territorial eagles also protects floaters.